1983
DOI: 10.1084/jem.158.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an active disaccharide unit of a glycoconjugate receptor for pneumococci attaching to human pharyngeal epithelial cells.

Abstract: Glycoconjugates containing the disaccharide unit GlcNAc beta 1 leads to 3Gal beta were suggested as receptors for pneumococci adhering to human pharyngeal epithelial cells. The receptor activity was detected both by inhibition of adhesion by an excess of free oligosaccharide and by induction or increase of adhesion after coating of target cells with glycolipid. Studies with free natural and synthetic oligosaccharides identified the disaccharide GlcNAc beta 1 leads to 3Gal beta as one critical binding site. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
150
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(151 citation statements)
references
References 40 publications
0
150
0
1
Order By: Relevance
“…Though Selinger and Reed (1979) proposed that the ability of S. pneumoniae to adhere to oropharyngeal cells might not be associated with virulency, Andersson et al (1981), have suggested that adherence of S. pneumoniae to oropharyngeal cells is an important step in the pathogenesis of otitis media, since this organism adhered avidly to pharyngeal cells from otitis media patients in an in vitro assay. They also have suggested that S. pneumoniae binds specifically to glycoconjugate receptors containing the disaccharide GIcNAcfll-~3Galfl (Andersson et al 1983). More recently, they demonstrated inhibition of S. pneumoniae attachment to pharyngeal cells by and nasal cultures human milk (Andersson et al 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Though Selinger and Reed (1979) proposed that the ability of S. pneumoniae to adhere to oropharyngeal cells might not be associated with virulency, Andersson et al (1981), have suggested that adherence of S. pneumoniae to oropharyngeal cells is an important step in the pathogenesis of otitis media, since this organism adhered avidly to pharyngeal cells from otitis media patients in an in vitro assay. They also have suggested that S. pneumoniae binds specifically to glycoconjugate receptors containing the disaccharide GIcNAcfll-~3Galfl (Andersson et al 1983). More recently, they demonstrated inhibition of S. pneumoniae attachment to pharyngeal cells by and nasal cultures human milk (Andersson et al 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Human colostrum and milk inhibit pneumococcal colonization (19), and each contains neolactotetraose and lactotetraose (16,19). Both sugars contain the GlcNAc␤1-3Gal␤ disaccharide, which can inhibit attachment of pneumococci to human pharyngeal cells (20) and may contribute to the ability of breast-feeding to reduce pneumococcal colonization and otitis media (21, †).…”
mentioning
confidence: 99%
“…Neolacto recognition has previously been described for other microbes and microbial toxins, such as, dengue virus (22), S. pneumoniae (23), N. meningitidis (24), H. influenzae (24), H. pylori (25), and the heat-labile enterotoxin of E. coli (LT) (26). Dissociation constants have not been determined for any of these interactions, thus it is not known whether they represent low-affinity binding as in the case of RF Borrelia.…”
Section: Discussionmentioning
confidence: 99%